Penerapan Problem Based Learning Terintegrasi STEAM untuk Meningkatkan Kemampuan 4C Siswa - Angga, Angga (Jurnal Didaktika Pendidikan Dasar, 2022)
This research based on the findings which showed that the 4C (Communication, Collaboration, Creativity and Innovation, Critical Thinking and Problem Solving) skills of third grade students at SDN 1 Sukarame. The purpose of this research is to improve the students 4C skills. The learning models that can improve students 4C skills to have 4C skills is the Problem Based Learning (PBL) model. The learning approach that can be integrated with the PBL model is the STEAM approach (Science, Technology, Engineering, Art, Mathematics). The method used in this research is a quantitative method, while the design used is Classroom Action Research (CAR). Based on the results of this study, the author applies the STEAM-integrated PBL model in learning on the material for the Concept of Change Objects in class III SDN 1 Sukarame. The results of the learning implementation show that the application of the STEAM integrated PBL model can improve the 4C ability of third grade elementary school students. PBL syntax is implemented with a percentage of 100%. The posttest results showed 90% of students achieved scores above the KBM. All groups get scores above 80. In addition, students 4C ability results in N-gain of 0.57 or 57%.